2014
DOI: 10.1002/elan.201300650
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Graphene‐Based Sensors on the Redox Mechanism of Aspirin

Abstract: The electrochemical behavior of aspirin at a graphene modified glassy carbon electrode has been investigated using cyclic and differential pulse voltammetric techniques. The dependence of the current on pH, concentration and scan rate was investigated to optimize the experimental conditions for determination of aspirin. A plausible oxidation mechanism was proposed. Under the optimum conditions, the oxidation peak current was linearly proportional to the concentration of aspirin in the range from 1.00×10−6 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This then rearranges further with one electron transfer to yield 2, 5-dihydroxybenzoic acid as the final product. Thus, the mechanism of the redox process of CF and ASA is proposed in Scheme 1 , based on the previous literature [18,41,42] .…”
Section: Effects Of Ph and Scan Ratementioning
confidence: 99%
“…This then rearranges further with one electron transfer to yield 2, 5-dihydroxybenzoic acid as the final product. Thus, the mechanism of the redox process of CF and ASA is proposed in Scheme 1 , based on the previous literature [18,41,42] .…”
Section: Effects Of Ph and Scan Ratementioning
confidence: 99%
“…Dropsens.com). A critical advantage of the system advocated here is the fact that the sensor does not require extensive modification with nanoparticles [18,19], graphene [23,24] or enzymes [25]. The reagentless nature provides a procedurally simple solution with a clear analytical signal arising from the dimer's reduction peak process.…”
Section: Discussionmentioning
confidence: 99%
“…The application of electrochemical techniques to the detection of salicylic acid has traditionally been beset by a number of issues -mainly the large anodic potentials required to oxidise the analyte and the subsequent fouling of the electrode by oligomeric/polymeric oxidation products. A variety of approaches have been taken to minimise the effects of the latter and include: carbon electrodes [17], carbon with gold/iron oxide nanoparticles [18], gold electrodes coated with copper nanoparticles [19], platinum electrodes [20,21], screen printed electrodes [22], graphene based systems [23,24] and enzyme electrodes [25,26]. Park and Eun (2016) have postulated that while passivating polymeric films can arise, a number of additional products will also be formed [27] and the various possibilities are outlined in Scheme 2.…”
Section: Methodsmentioning
confidence: 99%
“…Banks and Brownson (2010) demonstrated that the enhanced electron transfer of graphene occurs at its edge, and the presence of oxygen-containing groups at its edges can influence the adsorption/desorption of molecules that takes place before and after an electrochemical reaction. Moreover graphene has been used in the preparation of electrochemical sensor (Huang et al, 2013;Patil et al, 2014). Owing to the unique properties of large surface area, excellent conductivity, good chemical stability and easy fabrication, graphene oxide (GO) has been the star material in a variety of material sciences, electronic devices, sensors and electrocatalysis (Ai et al, 2014;Prabakaran and Pandian, 2015;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 97%